Integrating Artificial Intelligence into Entrepreneurship Education for Engineering Graduates in Nigeria - Najeem Olawale Adelakun; Samaila Mande (LPPM Universitas Andalas, 2026)
Artificial Intelligence (AI) is rapidly transforming the world of education, innovation and entrepreneurship; in the field of engineering education, AI has become an accelerator and a mediator - helping eliminate the divide between theory and practice, as well as between academic knowledge and that which is applicable in industry. The study examines the possibility of artificial intelligence integration in order to expand entrepreneurial skill, human capital, and innovation systems within Nigerian tertiary institutions. The study explores the effect of cluster formation, enabling environments, workforce retention, and AI adoption on entrepreneurial performance through a mixed-method approach, where quantitative data reveal that AI-enriched learning environments and the use of AI-enhanced learning environments have a strong positive relationship with entrepreneurial performance, and qualitative information indicates that intelligent systems are enabling factors influencing entrepreneurial performance in terms of creativity, employability, and collaboration. The results of the study show that AI-based entrepreneurship education can increase the application of practical problem-solving, intelligent mentoring, and data-based policy design of sustainable development. The research concludes that implementing AI in engineering programs has the potential to revolutionize Nigeria human capital base by eliminating skills shortages and enhancing the growth of an innovation-driven economy.